Miss Spider$1 (Bs new car s - Kirk, David, 1955- (New York : Scholastic Press, 1997)
Miss Spider and her husband go shopping for a car.
Keywords: Spiders -- Fiction; Insects -- Fiction; Automobiles -- Fiction; Shopping -- Fiction; Stories in rhyme